Comparative Study Between Northup’s Narrative Slave “Twelve Years a Slave” and Its Adapted Movie - Susi Astiantih (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
Literary work and movie have their own characteristics even though both have the same storyline. Literary work reveal the story in narrative form while movie, reveal the story through audio and visual.Today many literary works adapted into movie.One of literary works adapted into movie is Twelve Years a Slave. Twelve Years a Slave is a work was written by Solomon Northup which is based on his journey life when he was become slave for twelve years. This work was adapted into movie, in 2013 with the same title. This study aims to find the differences and similarities of both version of literary work and its movie and to identify the process of adapting  of literary work (narrative slave)  into  adaptation work (movie). The method used was document analysis and showcase the screenshot with using the structuralism which focus on the intrinsic elements of the story and comparing it with intrinsic elements on movie adaptation.This data analysis shows that there are many changes that occur in the adaptation work during the adaptation process.That was because the changes of medium and how to deliver the message be adjusted with duration and the existence of other supporting things such as the addition, reduction and improvisation of the scene.